Calves grazing on prairie dog town - Gunther, Deb, photographer (Colorado State University. Libraries, 2001)
Three calves resting, grazing and frolicking on SGS with prairie dog burrow in foreground (132k file).
Keywords: prairie dog town; SGS; cattle; animals